A 96‐hour continuous wound infiltration with ropivacaine reduces analgesic consumption after liver resection: A randomized, double‐blind, controlled trial. Issue 1 (27th November 2018) - Peres‐Bachelot, Véronique; Blanc, Ellen; Oussaid, Nadia; Pérol, David; Daunizeau‐Walker, Anne Laure; Pouderoux, Stéphanie; Peyrat, Patrice; Rivoire, Michel; Dupré, Aurélien
Abstract : Background: Continuous wound infiltration (CWI) with local anesthetics to reduce morphine consumption in postoperative pain management after open liver resection in patients with cancer. Methods: This single‐center randomized double‐blind study allocated patients requiring resection of liver metastases to receive a 3.75 mg/mL ropivacaine (ROP) infiltration, followed by a 2 mg/mL ROP CWI, or placebo (P) for 96 hours. Postoperative analgesia included acetaminophen and patient‐controlled analgesia morphine pump. The primary endpoint was to investigate the reduction of total morphine consumption (mg/kg) over the first 96 postoperative hours. Results: Eighty‐five patients were recruited, and randomized (ROP: 42, P: 43) between 2009 and 2014. The median morphine consumption significantly decreased in the ROP arm in the first 96 postoperative hours (ROP: 1.0, P: 1.5 mg/kg; P  = 0.026). Twenty‐three (27%) patients had grade 3 adverse events (ROP: 14, P: 9) and four experienced grade 3 treatment‐related adverse events (ROP: mental confusion [n = 1], hallucinations [n = 2], P: hematoma [n = 1]). Two (5%) patients showed a wound inflammation (ROP: 1, P: 1). Nine (11%) patients experienced at least one serious adverse event (ROP: 6, P: 3); none related to treatment. Conclusion: Preperitoneal CWI of 2 mg/mL ROP significantly reduces intravenous morphine consumption during the 96 postoperative hours resulting in an absolute reduction of 0.5 mg/kg.